Choosing a Model for eConsult Specialist Remuneration: Factors to Consider - Clare Liddy (Informatics, 2016)
Electronic consultation (eConsult) is an innovative solution that allows specialists and primary care providers to communicate electronically, improving access to specialist care. Understanding the cost implications of different remuneration models available to pay specialists is of critical importance as adoption of these services continues to increase. We used data collected through the Champlain BASE (Building Access to Specialists through eConsultation) eConsult service to simulate the cost implications of different remuneration models in Canada. The prorated hourly rate model averaged $45.72 CAD (Canadian Dollar) per eConsult while the prorated hourly rate with incentive averaged $51.90 CAD per eConsult, and the fee for service cost $60.50 CAD per eConsult. Paying all specialty groups to block three hours per week for eConsults averaged $337.44 CAD per eConsult and paying for 1-h blocks averaged $133.41 CAD per eConsult. As the remuneration of specialists is the largest cost driver of an established eConsult service, our findings can inform policymakers considering the implementation of eConsult or wishing to further develop an existing service.